2006
DOI: 10.1381/096089206777822205
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Gastric Banding in the Rat Model as a Means of Videolaparoscopic Training

Abstract: The development of laparoscopy in bariatric surgery has attracted a large number of surgeons. Learning this method for future clinical practice requires intensive training with inert tissues, simulators and experimental surgery in animals. Performing these procedures in small animals, with the same equipment used in humans, is feasible, allowing familiarization with and comprehension of the basic techniques. Wistar rats weighing 300-600 g were used. The animals were kept in standard laboratory conditions. A la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…23 Although considerable basic research on RYGBP using animal models has been conducted, 16,[24][25][26] animal models of gastric banding are very limited. 11,19 Bozbora et al 12 estimated the materials of gastric banding for gastric and esophageal mucosa of Wistar rats. De Monteiro et al 11 established an animal model of gastric banding using Wistar rats, and showed a decrease in both cumulative weight gain and food intake.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…23 Although considerable basic research on RYGBP using animal models has been conducted, 16,[24][25][26] animal models of gastric banding are very limited. 11,19 Bozbora et al 12 estimated the materials of gastric banding for gastric and esophageal mucosa of Wistar rats. De Monteiro et al 11 established an animal model of gastric banding using Wistar rats, and showed a decrease in both cumulative weight gain and food intake.…”
Section: Discussionmentioning
confidence: 99%
“…De Monteiro et al 11 established an animal model of gastric banding using Wistar rats, and showed a decrease in both cumulative weight gain and food intake. Additionally, de Menze Ettinger et al 19 performed laparoscopic gastric banding in Wistar rats as a means of video-laparoscopic training. Reports on gastric banding rat models are increasing, but to the best of our knowledge, there have been no reports on improvements in metabolic parameters or on the detailed procedures of the gastric banding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several rat models of gastric banding have recently been reported [10,12,13,14,15], and their food intake and body weight gain has been found to be less than that of sham-operated rats [12,13]. Complete inhibition of weight gain was not observed in any of the models [16], and even in obese Zucker rats gastric banding was found to result in a decrease in weight gain and food intake rather than in absolute weight [15].…”
Section: Discussionmentioning
confidence: 99%